Tanshinone I attenuates the malignant biological properties of ovarian cancer by inducing apoptosis and autophagy via the inactivation of PI3K/AKT/mTOR pathway - Zhou, Jin; Jiang, Yuan‐yuan; Chen, Huan; Wu, Yi‐chao; Zhang, Li (Cell proliferation, 2020)
Objectives Tanshinone I (Tan‐I) is one of the vital fatsoluble monomer components, which extracted from Chinese medicinal herb Salvia miltiorrhiza Bunge. It has been shown that Tan‐I exhibited anti‐tumour activities on different types of cancers. However, the underlying mechanisms by which Tan‐Ⅰ regulates apoptosis and autophagy in ovarian cancer remain unclear. Thus, this study aimed to access the therapy effect of Tan‐Ⅰ and the underlying mechanisms. Methods Ovarian cancer cells A2780 and ID‐8 were treated with different concentrations of Tan‐Ⅰ (0, 1.2, 2.4, 4.8 and 9.6 μg/mL) for 24 hours. The cell proliferation was analysed by CCK8 assay, EdU staining and clone formation assay. Apoptosis was assessed by the TUNEL assay and flow cytometry. The protein levels of apoptosis protein (Caspase‐3), autophagy protein (Beclin1, ATG7, p62 and LC3II/LC3I) and PI3K/AKT/mTOR pathway were determined by Western blot. Autophagic vacuoles in cells were observed with LC3 dyeing using confocal fluorescent microscopy. Anti‐tumour activity of Tan‐Ⅰ was accessed by subcutaneous xeno‐transplanted tumour model of human ovarian cancer in nude mice. The Ki67, Caspase‐3 level and apoptosis level were analysed by immunohistochemistry and TUNEL staining. Results Tan‐Ⅰ inhibited the proliferation of ovarian cancer cells A2780 and ID‐8 in a dose‐dependent manner, based on CCK8 assay, EdU staining and clone formation assay. In additional, Tan‐Ⅰ induced cancer cell apoptosis and autophagy in a dose‐dependent manner in ovarian cancer cells by TUNEL assay, flow cytometry and Western blot. Tan‐Ⅰ significantly inhibited tumour growth by inducing cell apoptosis and autophagy. Mechanistically, Tan‐Ⅰ activated apoptosis‐associated protein Caspase‐3 cleavage to promote cell apoptosis and inhibited PI3K/AKT/mTOR pathway to induce autophagy. Conclusions This is the first evidence that Tan‐Ⅰ induced apoptosis and promoted autophagy via the inactivation of PI3K/AKT/mTOR pathway on ovarian cancer and further inhibited tumour growth, which might be considered as effective strategy.